Regional-Scale In-Depth Analysis of Soil Fungal Diversity Reveals Strong pH and Plant Species Effects in Northern Europe - Tedersoo, Leho; Anslan, Sten; Bahram, Mohammad; Drenkhan, Rein; Pritsch, Karin; Buegger, Franz; Padari, Allar; Hagh-Doust, Niloufar; Mikryukov, Vladimir; Gohar, Daniyal; Amiri, Rasekh; Hiiesalu, Indrek; et al. (Frontiers in Microbiology, 2020)
Soil microbiome has a pivotal role in ecosystem function, yet little is known about its build-up from local to regional scales. In a multi-year survey involving 1251 plots and long-read third-generation sequencing, we found that soil pH has the strongest effect on the diversity of fungi and its multiple taxonomic and functional groups. The pH effects were typically unimodal, usually both direct and indirect through tree species, soil nutrients or mold abundance. Individual tree species, particularly Pinus sylvestris, Picea abies and Populus x wettsteinii, and overall ectomycorrhizal plant proportion had relatively stronger effects on the diversity of biotrophic fungi than saprotrophic fungi. In contrast to expectations, diversity of soil fungi tended to be higher in forest island habitats potentially due to the edge effect, but fungal richness declined with island distance and in response to forest fragmentation. Virgin forests supported somewhat higher fungal diversity than old non-pristine forests, but there were no differences in richness between natural and anthropogenic habitats such as parks and coppiced gardens. Diversity of most fungal groups suffered from management of seminatural woodlands and parks and forests, but especially for forests the results depended on fungal group and time of partial harvesting. We conclude that the positive effects of tree diversity on overall fungal richness represent a combined niche effect of soil properties and intimate associations.